Jenis-jenis Makrozoobentos yang Ditemukan di Batang Kuantan Kawasan Wisata Geopark Silokek Kabupaten Sijunjung - Ramadhani, Annisa; Widiana, Rina; Abizar, Abizar (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The Kuantan River in the Silokek Geopark Tourism Area, Sijunjung Regency, shows that the condition of the Kuantan River in the Silokek Geopark Tourism Area is a natural and potential tourism area, because the Kuantan River in the Silokek Geopark Tourism Area has become a tourist attraction due to its abundant natural wealth. However, gold mining has caused the Kuantan River water to be categorized as polluted, indicated by its turbidity. This study aims to determine the types of macrozoobenthos found in the Kuantan River within the Silokek Geopark Tourism Area, Sijunjung Regency. This research was conducted from August to December 2023. The research used a descriptive survey method, which included direct observation and sampling at the research site. The sampling technique used was purposive sampling, selecting three research stations. Sample identification was conducted at the Biology Education Laboratory, Universitas PGRI Sumatera Barat. Physicochemical water measurements were carried out at the Laboratory of Standardization and Industrial Services in Gadut, Padang, West Sumatra. The results of the research on the types of macrozoobenthos found in the Kuantan River within the Silokek Geopark Tourism Area, Sijunjung Regency, identified 10 species belonging to 2 classes: Gastropoda and Pelecypoda. Eight species of Gastropoda were found: Tarebia granifera, Thiara scabra, Brotia costula, Tryonia clathrata, Pleurocera acuta, Thiara scabra, Goniobasis livescens, Brotia sp., and 2 species of Pelecypoda: Corbicula manilensis and Pilsbryoconcha exilis.